KEBIJAKAN MANAJEMEN TRANSPORTASI DARAT DAN DAMPAKNYA TERHADAP PEREKONOMIAN MASYARAKAT DI KOTA DEPOK - Kadarisman, Muh; Gunawan, Aang; Ismiyati, Ismiyati (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
In achieving Depok City development, the role of land transport has an important and strategic position, so that policies need to be integrated in a single management policy and land transportation impact on the economy of the community in Depok. Various policies have been issued, in order to minimize the land transport problems, but no matter how well the policy will not work optimally for the management of land transportation is less addressed. This study used descriptive qualitative, because trying to find empirical facts with the proper interpretation of the action phenomenon. Results: 1. Selection land transportation that correspond to the characteristics of Depok City, and attentive to the needs and interests of all sections of society were different, able to support the effectiveness and efficiency of the provision of public transport services of the city. 2. Development of an adequate road network in the City of Depok has increased the economic sectors of society, increasing the value / price of land, the development of small-scale enterprises, medium and large, the product specialization between regions, the concentration and urbanization, especially in areas that have opened access roads and transport. Resulting in increased revenue Depok City coupled with equitable distribution of goods between residents, business lines spread across several regions. In addition, an increasing number and types of goods and services are able to produce consumer, government and industry.